QUAS-R: An SLC1A5-mediated glutamine uptake assay with single-cell resolution reveals metabolic heterogeneity with immune populations - Leonard R. Pelgrom; Gavin M. Davis; Simon O’Shaughnessy; Emilie J.M. Wezenberg; Sander I. Van Kasteren; David K. Finlay; Linda V. Sinclair (Cell Reports, 2023)
Summary: System-level analysis of single-cell data is rapidly transforming the field of immunometabolism. Given the competitive demand for nutrients in immune microenvironments, there is a need to understand how and when immune cells access these nutrients. Here, we describe a new approach for single-cell analysis of nutrient uptake where we use in-cell biorthogonal labeling of a functionalized amino acid after transport into the cell. In this manner, the bona fide active uptake of glutamine via SLC1A5/ASCT2 could be quantified. We used this assay to interrogate the transport capacity of complex immune subpopulations, both in vitro and in vivo. Taken together, our findings provide an easy sensitive single-cell assay to assess which cells support their function via SLC1A5-mediated uptake. This is a significant addition to the single-cell metabolic toolbox required to decode the metabolic landscape of complex immune microenvironments.